2015
DOI: 10.1210/jc.2014-4337
|View full text |Cite
|
Sign up to set email alerts
|

Glycogenin-2 Is Dispensable for Liver Glycogen Synthesis and Glucagon-Stimulated Glucose Release

Abstract: This is the first evaluation of humans without GN2 expression. Our data indicate that GN2 is not required for liver glycogen synthesis and glucagon-stimulated glucose release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Another group studied the effect of a similar deletion on liver function (11 members of two families and one blood donor) and found no gross abnormalities. 9 Although their assay lacked the resolution to define the breakpoints of the deletion, their results were compatible with the esv2662319 deletion. XG is homologous to CD99 and therefore it is speculated they share similar cell adhesion and migration functions.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Another group studied the effect of a similar deletion on liver function (11 members of two families and one blood donor) and found no gross abnormalities. 9 Although their assay lacked the resolution to define the breakpoints of the deletion, their results were compatible with the esv2662319 deletion. XG is homologous to CD99 and therefore it is speculated they share similar cell adhesion and migration functions.…”
Section: Discussionmentioning
confidence: 91%
“…Mensah et al found no clinical abnormalities in the participants of their study; however, they did not investigate if these persons had intact XG or GYG2 . Another group studied the effect of a similar deletion on liver function (11 members of two families and one blood donor) and found no gross abnormalities . Although their assay lacked the resolution to define the breakpoints of the deletion, their results were compatible with the esv2662319 deletion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, no impact on liver function has been reported, and glycogen storage such as seen in the biopsy from patient 1 may be subclinical. This may be due to glycogenin-2 that is expressed in the liver, although the importance of glycogenin-2 has been debated (Irgens et al 2015). In previously described patients, at least 32 loss-of-function (nonsense and splice site) variants in the 38 GYG1 alleles were identified.…”
Section: Discussionmentioning
confidence: 99%